An Empirical Study of Word of Mouth Strategies and Positive Recommendation Intentions in Private High Schools - Laurencia Anindiya Agustine Puspita Sari; Catur Widayati; Purnamawati Helen Widjaja; Dekrita Putri Puspa Wijaya (Dinasti Review, 2026)
Education is very necessary for the community to avoid ignorance, therefore competition also exists at the high school level, especially for private schools where one competes with another to get prospective students who will later become the best graduates. This study aims to analyze and test the influence of e-service quality variables, positive WOM, customer trust. The entire object that is the main focus is private high school students in Tangerang City. Sampling uses a purposive sampling method based on certain criteria such as distributing questionnaires with several related statements about things based on existing indicator variables and using a quantitative method with a causal approach between the independent variables and the dependent variables used in the study, which is calculated using the Slovin formula because the number of populations is known so that the existing sample after being calculated is 390. And this study uses the Smart PLS ver 4.0.9.6 analysis method. The results of the existing hypothesis test, it shows that the E-Service Quality and Customer Trust variables have significant positive results on the Positive Word of Mouth variable. The existing findings indicate that if the school provides good service, it will gain consumer trust which will later lead to positive reviews from consumers to others.